A study on postoperative nursing of minimally invasive surgery for lumbar disc herniation - QUAN,Weiwei (2022)
Abstract In order to explore the effective nursing methods and clinical therapeutic effects for patients with lumbar disc herniation after receiving minimally invasive surgery. In this study, a total of 50 patients receiving minimally invasive surgery for lumbar disc herniation in our hospital over the past year were selected and randomly divided into trial group and control group, with 25 patients in each group. Patients in control group were given routine nursing, and those in trial group were given postoperative comprehensive nursing including postoperative rehabilitation exercise, psychological nursing, diet nursing and other aspects. Visual analogue scale (VAS) was used to score the pain of patients in both groups before and after surgery; The final result shown that patients in trial group had better postoperative recovery time and hospital stays than patients in control group after nursing, with statistically significant difference (P < 0.05); the score of visual analogue scale (VAS) in trial group was better than that in control group, and with statistically significant difference (P < 0.05); the effective rate of trial group was 92.5%, compared with the 75% of control group with statistically significant difference (P < 0.05); the score of Barthel index of trial group was obviously better than that of control group, with statistically significant difference (P < 0.05). Therefore, the postoperative comprehensive nursing can not only help to improve the postoperative therapeutic effect, but also reduce the pain, accelerate the postoperative recovery and shorten the hospital stays of patients. Therefore, it shall be paid attention to and widely used in clinical practice.